Optimal fiscal policy in a model with reciprocity in labor relations: the case of Bulgaria - Aleksandar Vasilev (Journal of Economic and Administrative Sciences, 2022)
Purpose: This paper explores the effects of fiscal policy in an economy with reciprocity in labor relations and fair wages, consumption taxes and a common income tax rate in place. Design/methodology/approach: To this end, a dynamic general-equilibrium model with government sector is calibrated to Bulgarian data (1999–2018). Two regimes are compared and contrasted – the exogenous (observed) vs optimal policy (Ramsey) case. The focus of the paper is on the relative importance of consumption vs income taxation, as well as on the provision of utility-enhancing public services. Bulgarian economy was chosen as a case study due to its major dependence on consumption taxation as a source of tax revenue. Findings: (1) The optimal steady-state income tax rate is zero; (2) the benevolent Ramsey planner provides the optimal amount of the utility-enhancing public services, which are now three times lower; (3) the optimal steady-state consumption tax needed to finance the optimal level of government spending is 18:7%. Originality/value: This is the first study on optimal fiscal policy with reciprocity in labor relations.
Keywords: E24; E32; 330; Ramsey policy; general equilibrium